Optimisation of biomass and lipid production of a tropical thraustochytrid Aurantiochytrium sp. UMACC-T023 in submerged-liquid fermentation for large-scale biodiesel production / Mohamad Nor Azzimi Sohedein - Mohamad Nor Azzimi , Sohedein (2020)
A tropical thraustochytrid, Aurantiochytrium sp. UMACC-T023, was optimised for high biomass and lipid production in submerged-liquid fermentation (SLF). Biomass and lipid production were optimised based on glucose, polypeptone, and yeast extract concentration using response surface methodology (RSM). In RSM, the applied central composite design (CCD) showed that the optimisation model was significant for all variables studied. Yeast extract and polypeptone were associated with significant effects in UMACC-T023 biomass production with p < 0.05. The model was validated by employing the optimised media composition in shake flasks and in 1.4-L stirred-tank bioreactors. The optimised media composition for both biomass and lipid production was 10 g L-1 glucose, 15.08 g L-1 polypeptone, and 13.56 g L-1 yeast extract. Biomass production in the bioreactor increased 2.12-fold compared with the shake flask culture utilising the same optimised media composition. This result demonstrated that the optimized media composition can be utilised for large-scale lipid production of UMACC-T023 for potential biodiesel feedstock as it also fulfilled the international standards for biodiesel.